81 The living well group: a public partnership initiative to improve end of life care in an acute hospital. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Pharaoh, Amy; Hunt, Clive
Abstract : Background: Poole Hospital NHS Foundation Trust is participating in Building on the best (Botb) – a national initiative to improve end of life care in acute hospitals. The Ambitions Framework recognises the important role of partnerships between communities and professional services. A Public Partnership Group was created to support delivery of the projects comprising Botb. Methods: The group was recruited to following an article in the local press entitled: 'Poole Hospital wants to improve its end of life care. Can you help make it even better?' The public were invited to respond to the article by email. Respondents were screened and if thought suitable for inclusion in the group, were invited along for the inaugural meeting in January 2017. The group collectively decided to name themselves The Living Well Group and have continued to meet on a six weekly basis for a two hour meeting facilitated by a Palliative Care Consultant and Transformation Manager in End of Life Care. Results: The Living Well Group has evolved into a dynamic source of opinions and ideas to represent the local population. They have contributed to the following initiatives: Raising awareness and promoting dignity and compassion in dying Design of a new Advance Care Planning document Ideas for a befriending service at end of life in the hospital Involving families in the care of dying patients – touch, mouth care and hearing Feasibility of creating a standard of time to administration of analgesia A patient experience of care questionnaire at end of life Conclusions: The public are willing to contribute directly to the development of end of life care initiatives and it is possible to create an effective working group following advertisement in the local press.